A history of European literature : the west and the world from antiquity to the present - Cohen, Walter (Oxford University Press, 2017)
Walter Cohen argues that the history of European literature and each of its standard periods can be illuminated by comparative consideration of the different literary languages within Europe and by the ties of European literature to world literature. World literature is marked by recurrent, systematic features, outcomes of the way that language and literature are at once the products of major change and its agents. Cohen tracks these features from ancient times to the present, distinguishing five main overlapping stages. Within that framework, he shows that European literatures ongoing internal and external relationships are most visible at the level of form rather than of thematic statement or mimetic representation. European literature emerges from world literature before the birth of Europe — during antiquity, whose Classical languages are the heirs to the complex heritage of Afro-Eurasia. This legacy is later transmitted by Latin to the various vernaculars. The uniqueness of the process lies in the gradual displacement of the learned language by the vernacular, long dominated by Romance literatures. That development subsequently informs the second crucial differentiating dimension of European literature: the multicontinental expansion of its languages and characteristic genres, especially the novel, beginning in the Renaissance. This expansion ultimately results in the reintegration of European literature into world literature and thus in the creation of todays global literary system. The distinctiveness of European literature is to be found in these interrelated trajectories.
Keywords: European literature : History and criticism; kirjallisuudenhistoria; Eurooppa